Sex Cord-Stromal Tumors of Testis: A Clinicopathologic and Follow-Up Study of 15 Cases in a High-Volume Institute of China - Huang, Yin; Chen, Bo; Cao, Dehong; Chen, Zeyu; Li, Jin; Guo, Jianbing; Dong, Qiang; Wei, Qiang; Liu, Liangren (Frontiers in Medicine, 2022)
Objectives: To reported the first series of testicular sex cord-stromal tumors (TSCSTs) with detailed clinicopathologic findings and long-term follow-up in the Chinese population. Patients and Methods: From 2008 to 2018, 15 patients with TSCST were included in our study. The tumors were analyzed for epidemiological parameters, clinical characteristics, tumor markers, therapy, and follow-up data. Results: The median age of patients was 28 years (range, 13-80 years). Para-aortic lymph nodes metastases were detected in 2 patients after radiological evaluation. Orchiectomy was performed in all patients and the median diameter of the tumor was 1.5 cm (range, 0.5-5.0 cm). Nine Leydig cell tumors, 5 Sertoli cell tumors, and 1 unclassified type were confirmed after pathologic evaluation. Thirteen patients (86.7%) were categorized as stage I and 2 patients (13.3%) were categorized as stage II. The median clinical follow-up was 39.0 months (range, 5-97 months), which showed 10 alive, including 1 patient with progression at 40 months after orchiectomy. The 3-year and 5-year progression free survival were 100% and 90.0%, respectively. Conclusions: TSCST at stage I and II is a rare subtype with benign behavior and favorable prognosis in Chinese population. However, lymph nodes metastases may be the dominant risk of TSCST patients.